Biodiversity of animals that are living on the surface of soil under the forest stands surrounding Japan Cave of BKPH Nglerak, North Lawu, Karanganyar - SUGIYARTO SUGIYARTO; DHINI WIJAYA; SUCI YULIATI RAHAYU (Biodiversitas Journal of Biological Diversity, 2002)
The study of animal biodiversity that lived on the surface of soil under the stands forest surround Japan Cave BKPH Nglerak, North Lawu, Karanganyar has bee done. Observations were conducted in 6 stations of different stands of forest. Animals were caught by pit fall trap method. In each catching was found about 22 animals consisting of 6 families with Simpsonâ€™s diversity index of 0.5. The result of identification indicates that those animals belong to 4 classes: Insects (9 orders), Arachnids (2 orders), Diplopods (2 orders), and Crustacean (1 order). The most diverse animals was found in the habitat of pine stands while the lowest one found in the habitat of cultivated plants.Â© 2002 Jurusan Biologi FMIPA UNS SurakartaKey words: biodiversity, surface soil animals, Japan Cave, Lawu.